LINGUISTIC LANDSCAPE OF NAMING PRACTICES AND CULTURAL VALUES OF BATAK TOBA RESTAURANTS - Devi Melisa Saragi (Proceeding of International Conference on Art, Language, and Culture, 2019)
This research aimed at the naming practices of traditional Toba restaurants located in Jakartaand identifying the strategy of naming them. The technique used in collecting the data were observing and note taking. All the data obtainedhave been classified into two speech accomodation strategies carried out by Giles et al (1991). Then, by the writer’s language intuition as a Toba native speaker, all the data were analyzed by using cultural perspectives in order to get the cultural values behind them. The first result of this research shows that the naming practices were derived from clan, family member, honourable person, friendship, places and plant, delicious flavour and good value, advice and wish, togetherness, solidarity and philopsophy, religion and possession, welcoming and serving.  It can be seen that the basis of the naming refers to concepts reflecting the values, local wisdom and world views which belong to Toba people. The second result was thatdivergence strategy using Bahasa Toba in the naming was found tobe dominant, while convergence strategy found used English, Bahasa Indonesia or even the combinations between Bahasa Indonesia-English and Toba Language-English as the basis of naming the restaurants.